Implementation of the C4.5 Algorithm to Predict Student Achievement at SMK Negeri 6 Surakarta - Putri, Giovanni Anggiesta; Maryono, Dwi; Liantoni, Febri (IJIE (Indonesian Journal of Informatics Education), 2020)
Data mining is a knowledge used to get information from multiple data. C.45 Algorithm is one of data mining algorithm to classify data to many categories. Implementation of data mining not only could be used in industrial section but it could be used to in educational section (educational data mining) to help teacher and student improve their learning quality. This research purposed to know the implementation of data mining to predict student achievement from many factors could be effected . The research use Knowledge Discovery in Database method and it would be analyzed by accuration calculated from classify model that be form. Result of the research is the rules that formed by the decision tree and it could predict student achievement . Teacher could use it to give special treatment to student who got not good prediction.